A flame retardant polyurethane material and its preparation method and application

By doping modified expandable graphite, silica, two-dimensional nano-TiO2 and flame-retardant silicone in polyurethane foam, a stable carbonization layer is formed, which solves the problem of flammability of polyurethane foam and achieves the improvement of efficient fire-retardant flame retardant performance , suitable for a variety of thermal insulation and thermal insulation applications.

CN116162224BActive Publication Date: 2025-01-17DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111416652.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-11-25
Publication Date
2025-01-17
Estimated Expiration
2041-11-25

AI Technical Summary

Technical Problem

The ultimate oxygen index (LOI) of rigid polyurethane foam plastics is only 18% to 20%, which is a flammable polymer material. It has poor fire resistance and flammability, and has fire safety hazards.

Method used

Polyester diol is doped and modified with expandable graphite, silica, and two-dimensional nano-TiO2 with flame retardant silicone, using it to accelerate the formation of a stable carbonization layer during combustion to prevent heat transfer. , achieve efficient fire resistance and flame retardant.

Benefits of technology

It significantly reduces the combustion time and heat release rate of polyurethane foam, improves its flame retardant performance, and makes it self-extinguishing. It is suitable for pipeline insulation, storage tank insulation and wall insulation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003375581920000101
    Figure BDA0003375581920000101
  • Figure HDA0003375581930000011
    Figure HDA0003375581930000011
  • Figure HDA0003375581930000012
    Figure HDA0003375581930000012
Patent Text Reader

Abstract

The present application discloses a flame retardant polyurethane material and its preparation method and application, including a polyurethane matrix and a flame retardant additive; the polyurethane matrix is ​​obtained by polymerization of polyester diol and isocyanate; the flame retardant additive includes flame retardant silicone and flaky material; the flaky material is selected from at least one of flame retardant expandable graphite and two-dimensional nano-sheet TiO2 or flaky silica; the flame retardant expandable graphite, flaky silica, and two-dimensional nano-sheet TiO2 are surface modified; the isocyanate is selected from at least one of TDI-80, TDI-65 and TDI-100. By utilizing the synergistic effect of flame retardant silicone and nanocomposite, the polyurethane molecular chain structure and the hybridization of nanomaterials are regulated, so that the prepared polyurethane foam has the excellent characteristics of uniform pores, high strength and good flame retardant performance, and has broad application prospects in the fields of pipeline insulation, storage tank insulation, and wall insulation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a flame retardant polyurethane material and a preparation method thereof, belonging to the technical field of polymer materials. Background Art

[0002] Polyurethane foam is one of the most widely used varieties of plastics. It has light weight, ultra-low temperature thermal conductivity, weather resistance and heat preservation, high-efficiency insulation, sound insulation, and waterproof and moisture-proof after curing. It has almost penetrated into all sectors of the national economy, especially in transportation, refrigeration, building walls, insulation and other fields. However, the limiting oxygen index (LOI) of rigid polyurethane foam is only 18% to 20%, which is a flammable polymer material. At present, polyurethane foam generally has poor fire resistance and easy combustion, which poses a safety hazard of fire. Domestic and foreign scholars have conducted a lot of research on the flame retardant modification of rigid polyurethane foam, including the preparation of additive flame retardant polyurethane by adding inorganic flame retardants, organic flame retardants and organic-inorganic composite flame retardant additives, and the preparation of reactive flame retardant polyurethane materials using polyols containing flame retardant elements. Compared with reactive flame retardants, additive types have the characteristics of low cost and simple processing. Summary of the invention

[0003] In response to the problems of poor fire resistance and easy combustion of polyurethane foam, the present application utilizes expandable graphite, silica, nano-TiO2 and flame-retardant silicone with a lamellar structure to dope and modify polyester diols. The synergistic effect of the lamellar structure of expandable graphite, silica and two-dimensional nano-TiO2 and the flame-retardant silicone is utilized to accelerate the formation of a stable carbonized layer during the combustion process, which can prevent heat from being transferred to the interior of the material, thereby playing a role in efficient fire prevention and flame retardancy.

[0004] According to one aspect of the present application, there is provided a polyurethane material, comprising a polyurethane matrix and a flame retardant additive;

[0005] The polyurethane matrix is ​​obtained by polymerizing polyester diol and isocyanate;

[0006] The flame retardant auxiliary agent includes flame retardant silicone and sheet material;

[0007] The sheet material is selected from at least one of flame-retardant expandable graphite and two-dimensional nanosheet TiO2 or sheet silica;

[0008] The flame retardant expandable graphite, lamellar silica and two-dimensional nano-lamellar TiO2 are surface-modified.

[0009] The polyester diol is obtained by the following steps:

[0010] The raw materials containing diol and dibasic acid are mixed with a catalyst to undergo esterification and polycondensation to obtain the polyester diol;

[0011] The diol is selected from at least one of ethylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 1,10-decanediol or diethylene glycol;

[0012] The dibasic acid is selected from at least one of furandicarboxylic acid and terephthalic acid;

[0013] The catalyst is a nano titanium dioxide catalyst;

[0014] The temperature of the esterification reaction is 120-240°C;

[0015] Optionally, the temperature of the esterification reaction is 120-130°C;

[0016] The sign of the end of the esterification reaction is that no more water is produced;

[0017] After the esterification reaction is completed, vacuum is applied to allow the polycondensation reaction to occur;

[0018] The vacuum degree of the polycondensation reaction is <200 Pa;

[0019] The temperature of the polycondensation reaction is 180-240°C;

[0020] The polycondensation reaction time is 1 to 2.5 hours;

[0021] The atmosphere of the esterification reaction is a nitrogen atmosphere;

[0022] The number average molecular weight of the polyester diol is 800-5000.

[0023] Specifically, the method comprises the following steps: in a nitrogen atmosphere, diol and dibasic acid react at 120-130° C., a nano-TiO2 catalyst is added, in the initial stage, a small amount of water is continuously generated in the reaction system, and the reaction is carried out until the system solution becomes clear and transparent, at which time almost no water is generated, the reaction system begins to be evacuated, the vacuum degree is <100 Pa, and the temperature is raised to 180-240° C., the reaction is carried out for 1-2.5 hours, and the hydroxyl value and acid value of the system are measured.

[0024] The isocyanate is selected from at least one of TDI-80, TDI-65 and TDI-100.

[0025] The lateral size of the flame-retardant expandable graphite is 1um to 500um; the lateral size of the two-dimensional nano-sheet TiO2 is 50nm to 2um; and the lateral size of the sheet silica is 1um to 500um.

[0026] The flame retardant silicone is selected from at least one of Dow Corning FCA-117 and Dow Corning FCA-107;

[0027] According to another aspect of the present application, a method for preparing the above-mentioned polyurethane material is provided, comprising the following steps:

[0028] (1) mixing raw materials containing isocyanate and flame retardant silicone to obtain a mixed solution A;

[0029] (2) mixing and stirring the raw materials containing the modifier and the sheet material to obtain a mixture B;

[0030] (3) The mixed solution A and the mixture B are mixed evenly, the polyester diol and the catalyst are added, and foaming is performed to obtain the polyurethane material.

[0031] In the mixed solution A described in (1), the content of isocyanate is 80-98 wt %;

[0032] The solvent is an alcohol aqueous solution; the alcohol in the alcohol aqueous solution is selected from 1,4-butanediol and / or ethanol; the volume ratio of alcohol to water in the alcohol aqueous solution is 2.6-1.2:1.

[0033] The modifier described in (2) is selected from 2-hydroxyethyl methacrylate phosphate and / or ethylene glycol methacrylate phosphate;

[0034] The mass of the modifier is 5‰ to 5% of the mass of the sheet material.

[0035] (3), wherein the catalyst is selected from stannous isooctanoate and / or triethylamine;

[0036] The mass of the catalyst is 1‰ to 1% of the mass of the polyester diol;

[0037] The mass of the polyester diol is 45% to 65% of the total weight of the mixed solution A and the mixture B;

[0038] The amount of the sheet material used is 5% to 15% of the total weight of the mixed solution A and the mixture B.

[0039] It also includes the ripening process;

[0040] The aging time is 5 to 24 hours;

[0041] The aging temperature is 60-100°C.

[0042] According to another aspect of the present application, there is provided an application of the above-mentioned polyurethane material or the polyurethane material prepared by the above-mentioned preparation method, characterized in that it is used for pipeline insulation, storage tank insulation or wall insulation.

[0043] The beneficial effects of this application include:

[0044] The flame-retardant polyurethane material provided by the present application, the flame-retardant expandable graphite and the flame-retardant silicone are compounded in the polyester polyol system by an in-situ compounding method or a solution blending method, and the flame retardancy of the polyurethane is regulated by adjusting the addition ratio of the flame-retardant expandable graphite and the flame-retardant silicone to the phosphorus-containing polyester polyol monomer. The present application uses expandable graphite, silica and two-dimensional nano-sheet TiO2 with natural lamellar structure and flame-retardant silicone to dope and modify the phosphorus-containing polyester polyol, and utilizes the synergistic effect of the lamellar structure of expandable graphite, silica and two-dimensional nano-TiO2 and flame-retardant silicone to accelerate the formation of a stable carbonized layer during the combustion process, which can prevent heat from being transferred to the inside of the material, and play a role in efficient fire prevention and flame retardancy. The polyurethane molecular chain structure is regulated and hybridized with the expandable graphite material, and the addition of expandable graphite and flame-retardant silicone reduces the burning time and ignition time of the polyurethane foam, greatly reduces the heat release rate and heat release amount, and causes the polyurethane to have self-extinguishing properties. The prepared polyurethane foam material has the excellent characteristics of uniform pores, high strength and good flame retardant performance, and has broad application prospects in the fields of pipeline insulation, storage tank insulation, and wall insulation. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1a , 1b 1c is an electron microscope image of the modified flame retardant expandable graphite, silica and two-dimensional nanosheet TiO2 in Modification Example 1. DETAILED DESCRIPTION

[0046] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0047] Unless otherwise specified, the raw materials, monomers and flame retardant additives in the examples of the present application were purchased through commercial channels.

[0048] The two-dimensional nanosheet TiO2 is prepared by the method described in Example 1 of CN109837605B.

[0049] The analysis method in the examples of this application is as follows:

[0050] The method for determining the apparent density refers to the national standard: GB / T 6343-2009 Determination of the apparent density of foam plastics and rubber.

[0051] The reference standard for the dimensional stability test of rigid foam is: GB / T 8811-2008, Test method for dimensional stability of rigid foam plastics.

[0052] The compressive strength test of rigid foam refers to the standard: GB / T 8813-2008, Determination of compression properties of rigid foam plastics.

[0053] The flame retardant performance test method refers to the national standard: GB / T 2406-93, Plastic combustion performance test method oxygen index method.

[0054] Modification Example 1

[0055] The modifiers are added into the sheet materials (flame retardant expandable graphite, silica, two-dimensional nanosheet TiO2) respectively, and stirred and mixed for 0.2 to 1.0 hours.

[0056] The modifier is obtained by mixing 2-hydroxyethyl methacrylate phosphate and ethylene glycol methacrylate phosphate in a ratio of 2:1.

[0057] Figure 1a , 1b , 1c is an electron microscope image of modified flame-retardant expandable graphite, two-dimensional nanosheet TiO2, and silica;

[0058] It can be seen from the figure that the lamellar material still maintains a two-dimensional lamellar structure after being modified by the modifier.

[0059] Example 1

[0060] Preparation of polyester diol: Under nitrogen atmosphere, 8.6g ethylene glycol and 15.6g furandicarboxylic acid react at 120℃, and 80mg nano-TiO2 catalyst is added. In the initial stage of esterification reaction, a small amount of water is continuously generated in the reaction system. The reaction is carried out until the system solution is clear and transparent, and almost no water is generated. The reaction system begins to be evacuated, and the vacuum degree is <100Pa. The temperature is raised to 220℃, and the polycondensation reaction is carried out for 1.5 hours. The hydroxyl value of the system is measured to be 75mgKOH / g, and the acid value is 0.35mgKOH / g. It is recorded as polyester diol 1.

[0061] At room temperature of 25°C, 15.0g of isocyanate TDI-80, 1.2g of silicone FCA-117, and 1.2g of a mixed solution of 1,4-butanediol and water (2:1) were added, and stirred at room temperature until uniform, which was recorded as component A. Ethylene glycol methacrylate phosphate was added to 4.2g of expandable graphite (thickness 5um) and 0.5g of two-dimensional nano-TiO2 (thickness 50nm) at a mass ratio of 2:1. The mass of the two phosphates was 2.0% of the mass of the expandable graphite. Stir at high speed until the mixture was uniform, which was recorded as component B. After the mixed solution of A and B was mixed uniformly, 20.0g of polyester diol 1 and 0.03g of stannous isooctanoate catalyst were added, and the mixture was stirred quickly until uniform. The solution gradually foamed and quickly poured into the mold for static foaming. After the foaming was completed, it was aged for 24 hours to obtain a flame-retardant polyurethane foam material, which was recorded as sample 1#.

[0062] Example 2

[0063] Preparation of polyester diol: Under nitrogen atmosphere, 8.6g ethylene glycol and 15.6g furandicarboxylic acid react at 120℃, and 80mg nano-TiO2 catalyst is added. In the initial stage of esterification reaction, a small amount of water is continuously generated in the reaction system. The reaction is carried out until the system solution is clear and transparent, and almost no water is generated. The reaction system begins to be evacuated, and the vacuum degree is <100Pa. The temperature is raised to 220℃, and the polycondensation reaction is carried out for 1.5 hours. The hydroxyl value of the system is measured to be 75mgKOH / g, and the acid value is 0.35mgKOH / g. It is recorded as polyester diol 1.

[0064] At room temperature of 25°C, 15.0g of isocyanate TDI-80, 1.2g of silicone FCA-117, and 1.2g of a mixed solution of 1,4-butanediol and water (2:1) were added, and stirred at room temperature until uniform, which was recorded as component A. Methacrylate-2-hydroxyethyl phosphate and ethylene glycol methacrylate phosphate were added to 4.2g of expandable graphite (thickness 500um) and 0.5g of two-dimensional nano-TiO2 (thickness 50nm) at a mass ratio of 2:1. The mass of the two phosphates was 2.0% of the mass of the expandable graphite. They were stirred at high speed until uniformly mixed, which was recorded as component B. After the mixed solution of A and B was mixed uniformly, 20.0g of polyester diol 1 and 0.03g of stannous isooctanoate catalyst were added, and the mixture was stirred quickly until uniformly mixed. The solution gradually foamed and quickly poured into the mold for static foaming. After the foaming was completed, it was aged for 24 hours to obtain a flame-retardant polyurethane foam material, which was recorded as sample 2#.

[0065] Example 3

[0066] Preparation of polyester diol: Under nitrogen atmosphere, 8.6g ethylene glycol and 15.6g furandicarboxylic acid react at 120℃, and 80mg nano-TiO2 catalyst is added. In the initial stage of esterification reaction, a small amount of water is continuously generated in the reaction system. The reaction is carried out until the system solution is clear and transparent, and almost no water is generated. The reaction system begins to be evacuated, and the vacuum degree is <100Pa. The temperature is raised to 220℃, and the polycondensation reaction is carried out for 1.5 hours. The hydroxyl value of the system is measured to be 75mgKOH / g, and the acid value is 0.35mgKOH / g. It is recorded as polyester diol 1.

[0067] At room temperature of 25°C, 15.0g of isocyanate TDI-80, 1.8g of silicone FCA-117, and 1.2g of a mixed solution of 1,4-butanediol and water (2:1) were added, and stirred at room temperature until uniform, which was recorded as component A. Methacrylate-2-hydroxyethyl phosphate and ethylene glycol methacrylate phosphate were added to 4.2g of expandable graphite (thickness 500um) and 0.5g of two-dimensional nano-TiO2 (thickness 50nm) at a mass ratio of 2:1. The mass of the two phosphates was 2.0% of the mass of the expandable graphite. They were stirred at high speed until uniformly mixed, which was recorded as component B. After the mixed solution of A and B was mixed uniformly, 20.0g of polyester diol 1 and 0.03g of stannous isooctanoate catalyst were added, and the mixture was stirred quickly until uniformly mixed. The solution gradually foamed and quickly poured into the mold for static foaming. After the foaming was completed, it was aged for 24 hours to obtain a flame-retardant polyurethane foam material, which was recorded as sample 3#.

[0068] Example 4

[0069] Preparation of polyester diol: Under nitrogen atmosphere, 8.6g ethylene glycol and 15.6g furandicarboxylic acid react at 120℃, and 80mg nano-TiO2 catalyst is added. In the initial stage of esterification reaction, a small amount of water is continuously generated in the reaction system. The reaction is carried out until the system solution is clear and transparent, and almost no water is generated. The reaction system begins to be evacuated, and the vacuum degree is <100Pa. The temperature is raised to 220℃, and the polycondensation reaction is carried out for 1.5 hours. The hydroxyl value of the system is measured to be 67mgKOH / g, and the acid value is 0.3mgKOH / g. It is recorded as polyester diol 1.

[0070] At room temperature of 25°C, 15.0g of isocyanate TDI-80, 1.2g of silicone FCA-117, and 1.2g of a mixed solution of 1,4-butanediol and water (2:1) were added, and stirred at room temperature until uniform, which was recorded as component A. Methacrylate-2-hydroxyethyl phosphate and ethylene glycol methacrylate phosphate were added to 6.0g of expandable graphite (thickness 500um) and 0.5g of two-dimensional nano-TiO2 (thickness 50nm) at a mass ratio of 2:1. The mass of the two phosphates was 2.0% of the mass of the expandable graphite. They were stirred at high speed until uniformly mixed, which was recorded as component B. After the mixed solution of A and B was mixed uniformly, 20.0g of polyester diol 1 and 0.03g of stannous isooctanoate catalyst were added, and the mixture was stirred quickly until uniformly mixed. The solution gradually foamed and quickly poured into the mold for static foaming. After the foaming was completed, it was aged for 24 hours to obtain a flame-retardant polyurethane foam material, which was recorded as sample 4#.

[0071] Example 5

[0072] Preparation of polyester diol: Under nitrogen atmosphere, 8.6g ethylene glycol and 15.6g furandicarboxylic acid react at 120℃, and 80mg nano-TiO2 catalyst is added. In the initial stage of esterification reaction, a small amount of water is continuously generated in the reaction system. The reaction is carried out until the system solution is clear and transparent, and almost no water is generated. The reaction system begins to be evacuated, and the vacuum degree is <100Pa. The temperature is raised to 220℃, and the polycondensation reaction is carried out for 1.5 hours. The hydroxyl value of the system is measured to be 82mgKOH / g, and the acid value is 0.5mgKOH / g. It is recorded as polyester diol 1.

[0073] At room temperature of 25°C, 15.0g of isocyanate TDI-80, 1.2g of organosilicon FCA-117, and 1.2g of a mixed solution of 1,4-butanediol and water (2:1) were added, and stirred at room temperature until uniform, which was recorded as component A. Methacrylate-2-hydroxyethyl phosphate and ethylene glycol methacrylate phosphate were added to 4.2g of expandable graphite and 0.5g of two-dimensional nano-TiO2 (thickness 50nm) at a mass ratio of 2:1. The mass of the two phosphates was 2.0% of the mass of the expandable graphite. They were stirred at high speed until uniformly mixed, which was recorded as component B. After the mixed solution of A and B was mixed uniformly, 20.0g of polyester diol 1 and 0.03g of stannous isooctanoate catalyst were added, and the mixture was stirred quickly until uniformly mixed. The solution gradually foamed and quickly poured into the mold for static foaming. After the foaming was completed, it was aged for 24 hours to obtain a flame-retardant polyurethane foam material, which was recorded as sample 5#.

[0074] Example 6

[0075] Preparation of polyester diol: Under nitrogen atmosphere, 8.6g ethylene glycol and 16.6g terephthalic acid react at 120℃, add 80mg nano-TiO2 catalyst, esterification reaction in the initial stage, a small amount of water is continuously generated in the reaction system, the reaction is carried out until the system solution is clear and transparent, at which time almost no water is generated, the reaction system begins to be evacuated, the vacuum degree is <100Pa, and the temperature is raised to 220℃, the polycondensation reaction is carried out for 1.5 hours, the hydroxyl value of the system is measured to be 87mgKOH / g, and the acid value is 0.5mgKOH / g. It is recorded as polyester diol 2.

[0076] At room temperature of 25°C, 15.0g of isocyanate TDI-80, 1.2g of organosilicon FCA-117, and 1.2g of a mixed solution of 1,4-butanediol and water (2:1) were added, and stirred at room temperature until uniform, which was recorded as component A. Methacrylate-2-hydroxyethyl phosphate and ethylene glycol methacrylate phosphate were added to 4.2g of expandable graphite and 0.5g of two-dimensional nano-TiO2 (thickness 50nm) in a mass ratio of 2:1. The mass of the two phosphates was 2.0% of the mass of the expandable graphite. Stir at high speed until the mixture was uniform, which was recorded as component B. After the mixed solution of A and B was mixed uniformly, 20.0g of polyester diol 2 and 0.03g of stannous isooctanoate catalyst were added, and the mixture was stirred quickly until uniform. The solution gradually foamed and quickly poured into the mold for static foaming. After the foaming was completed, it was aged for 24 hours to obtain a flame-retardant polyurethane foam material, which was recorded as sample 6#.

[0077] Example 7

[0078] Preparation of polyester diol: Under nitrogen atmosphere, 8.6g ethylene glycol reacted with 8.4g terephthalic acid and 7.8g furandicarboxylic acid at 120°C, and 80mg nano-TiO2 catalyst was added. In the initial stage of esterification reaction, a small amount of water was continuously generated in the reaction system. The reaction was continued until the system solution was clear and transparent, and almost no water was generated. The reaction system began to be evacuated, and the vacuum degree was <100Pa. The temperature was raised to 220°C, and the polycondensation reaction was carried out for 1.5 hours. The hydroxyl value of the system was measured to be 57mgKOH / g, and the acid value was 0.5mgKOH / g. It was recorded as polyester diol 3.

[0079] At room temperature of 25°C, 15.0g of isocyanate TDI-80, 1.2g of organosilicon FCA-117, and 1.2g of a mixed solution of 1,4-butanediol and water (2:1) were added, and stirred at room temperature until uniform, which was recorded as component A. Methacrylate-2-hydroxyethyl phosphate and ethylene glycol methacrylate phosphate were added to 4.2g of expandable graphite and 0.5g of two-dimensional nano-TiO2 (thickness 50nm) at a mass ratio of 2:1. The mass of the two phosphates was 2.0% of the mass of the expandable graphite. They were stirred at high speed until uniformly mixed, which was recorded as component B. After the mixed solution of A and B was mixed uniformly, 20.0g of polyester diol 3 and 0.03g of stannous isooctanoate catalyst were added, and the mixture was stirred quickly until uniformly mixed. The solution gradually foamed and quickly poured into the mold for static foaming. After the foaming was completed, it was aged for 24 hours to obtain a flame-retardant polyurethane foam material, which was recorded as sample 7#.

[0080] Example 8

[0081] Preparation of polyester diol: Under nitrogen atmosphere, 4.3g ethylene glycol, 5.8g 1,4-butanediol and 15.6g furandicarboxylic acid were reacted at 120℃, and 80mg nano-TiO2 catalyst was added. In the initial stage of esterification reaction, a small amount of water was continuously generated in the reaction system. The reaction was carried out until the system solution was clear and transparent, and almost no water was generated. The reaction system began to be evacuated, and the vacuum degree was <100Pa. The temperature was raised to 220℃, and the polycondensation reaction was carried out for 1.5 hours. The hydroxyl value of the system was 52mgKOH / g, and the acid value was 0.25mgKOH / g. It was recorded as polyester diol 4.

[0082] At room temperature of 25°C, 15.0g of isocyanate TDI-80, 1.2g of organosilicon FCA-117, and 1.2g of a mixed solution of 1,4-butanediol and water (2:1) were added, and stirred at room temperature until uniform, which was recorded as component A. Methacrylate-2-hydroxyethyl phosphate and ethylene glycol methacrylate phosphate were added to 4.2g of expandable graphite and 0.5g of two-dimensional nano-TiO2 (thickness 50nm) at a mass ratio of 2:1. The mass of the two phosphates was 2.0% of the mass of the expandable graphite. They were stirred at high speed until uniformly mixed, which was recorded as component B. After the mixed solution of A and B was mixed uniformly, 20.0g of polyester diol 4 and 0.03g of stannous isooctanoate catalyst were added, and the mixture was stirred quickly until uniformly mixed. The solution gradually foamed and quickly poured into the mold for static foaming. After the foaming was completed, it was aged for 24 hours to obtain a flame-retardant polyurethane foam material, which was recorded as sample 8#.

[0083] Comparative Example 1

[0084] At room temperature of 25°C, 15.0g of isocyanate TDI-80 was added with 1.2g of a mixed solution of 1,4-butanediol and water (2:1), and stirred at room temperature until uniform, which was recorded as component A. 2-Hydroxyethyl methacrylate phosphate and ethylene glycol methacrylate phosphate were added to 4.2g of expandable graphite at a mass ratio of 2:1. The mass of the two phosphates was 2.0% of the mass of the expandable graphite. They were stirred at high speed until uniformly mixed, which was recorded as component B. After the mixed solution of A and B was mixed uniformly, 20.0g of polyester diol 1 and 0.03g of stannous isooctanoate catalyst were added, and the mixture was stirred rapidly until uniformly mixed. The solution gradually foamed and was quickly poured into the mold for static foaming. After the foaming was completed, it was aged for 24 hours to obtain a flame-retardant polyurethane foam material, which was recorded as sample D1#.

[0085] Comparative Example 2

[0086] At room temperature of 25°C, add 15.0g of isocyanate TDI-80, 1.2g of silicone FCA-117, and 1.2g of a mixed solution of 1,4-butanediol and water (2:1), stir and mix at room temperature until uniform, and record it as component A. Add 20.0g of polyester diol 1 and 0.03g of stannous isooctanoate catalyst to component A, stir quickly until the mixture is uniform, the solution gradually bubbles and is quickly poured into the mold for static foaming. After the foaming is completed, mature for 24 hours to obtain a flame-retardant polyurethane foam material, which is recorded as sample D2#.

[0087] The samples prepared in the above examples and comparative examples were tested for apparent density, compressive strength, dimensional stability and oxygen index. The results are shown in Table 1.

[0088] Table 1

[0089]

[0090] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A polyurethane material, characterized in that: It includes a polyurethane matrix and a flame retardant additive; The polyurethane matrix is ​​obtained by polymerizing polyester diol and isocyanate; The flame retardant auxiliary agent includes flame retardant silicone and sheet material; The sheet material consists of flame-retardant expandable graphite and two-dimensional nanosheet TiO2; The sheet material is surface modified; The modifier used for the surface modification is selected from 2-hydroxyethyl methacrylate phosphate and / or ethylene glycol methacrylate phosphate.

2. The polyurethane material according to claim 1, characterized in that: The polyester diol is obtained by the following steps: The raw materials containing diol and dibasic acid are mixed with a catalyst to undergo esterification and polycondensation to obtain the polyester diol; The diol is selected from at least one of ethylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 1,10-decanediol or diethylene glycol; The dibasic acid is selected from at least one of furandicarboxylic acid and terephthalic acid; The catalyst is a nano titanium dioxide catalyst; The temperature of the esterification reaction is 120-240°C; The sign of the end of the esterification reaction is that no more water is produced; After the esterification reaction is completed, vacuum is applied to allow the polycondensation reaction to occur; The vacuum degree of the polycondensation reaction is <200 Pa; The temperature of the polycondensation reaction is 180-240°C; The polycondensation reaction time is 1 to 2.5 hours; The atmosphere of the esterification reaction is a nitrogen atmosphere; The number average molecular weight of the polyester diol is 800-5000.

3. The polyurethane material according to claim 2, characterized in that: The temperature of the esterification reaction is 120-130°C.

4. The polyurethane material according to claim 1, characterized in that: The isocyanate is selected from at least one of TDI-80, TDI-65 and TDI-100.

5. The polyurethane material according to claim 1, characterized in that: The lateral size of the flame retardant expandable graphite is 1um~500um; the lateral size of the two-dimensional nano-sheet TiO2 is 50nm~2um; the lateral size of the silica sheet is 1um~500um; The flame retardant silicone is selected from at least one of Dow Corning FCA-117 and Dow Corning FCA-107.

6. The method for preparing the polyurethane material according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) mixing raw materials containing isocyanate and flame retardant silicone to obtain a mixed solution A; (2) mixing and stirring the raw materials containing the modifier and the sheet material to obtain a mixture B; (3) The mixed solution A and the mixture B are mixed evenly, the polyester diol and the catalyst are added, and foaming is performed to obtain the polyurethane material.

7. The preparation method according to claim 6, characterized in that: In the mixed solution A described in (1), the content of isocyanate is 80-98 wt %; The solvent is an alcohol aqueous solution; the alcohol in the alcohol aqueous solution is selected from 1,4-butanediol and / or ethanol; the volume ratio of alcohol to water in the alcohol aqueous solution is 2.6-1.2:

1.

8. The preparation method according to claim 6, characterized in that: The mass of the modifier described in (2) is 5‰~5% of the mass of the sheet material.

9. The preparation method according to claim 6, characterized in that: (3), wherein the catalyst is selected from stannous isooctanoate and / or triethylamine; The mass of the catalyst is 1‰~1% of the mass of the polyester diol; The mass of the polyester diol is 45% to 65% of the total weight of the mixed solution A and the mixture B; The amount of the sheet material used is 5% to 15% of the total weight of the mixed solution A and the mixture B.

10. The preparation method according to claim 6, characterized in that: (3) also includes the ripening process; The aging time is 5 to 24 hours; The aging temperature is 60-100°C.

11. Use of the polyurethane material according to any one of claims 1 to 5 or the polyurethane material prepared by the preparation method according to any one of claims 6 to 10, characterized in that: Used for pipe insulation, tank insulation or wall insulation.

Citation Information

Patent Citations

  • A two-dimensional ultrathin titanium dioxide modified polyester nanocomposite brush filament and its preparation method

    CN109837605B

  • Halogen-free flame retardant polyurethane flexible foam and preparation method thereof

    CN105131580A